Optimisation of design parameters for modular range enhanced projectile - Jelic, Z. (Cranfield University, 2016)
There is an underpinning requirement for artillery systems to achieve longer range, better precision, and an adequate lethal effect. The main objective of this research is to investigate various methods of range increase and propose optimal solution for range extension of existing artillery systems. The proposed solution is novel, modular projectile design. Several methodologies for projectile range increment (such as improved aerodynamics and ballistic profile) were combined to achieve the "goal'", but mainly work was concentrated on projectile's "assisted" propulsion with Base Bleed (BB) and Solid Rocket Motor (SRM). The gun's interior ballistics, i.e. ordnance parameters (propelling charge, volume of combustion chamber, length of the barrel and muzzle velocity) remains unchanged. The novel concept of modular design of an artillery projectile includes separate modules for propulsion, drag reduction, and payload. Various payload module configurations should allow diverse lethal effects, and four different propulsion configurations allow engagement of various targets. Among all "possible' projectile configurations, the focus was on arrangement that will fly longest from given ordnance, with fragmentation effect on target. To achieve projectile's "aims," it required development of new chemical composition for BB and SRM propellant. In addition, new type of BB propellant grain geometry was developed, for efficient base drag reduction (by injecting sufficient amount of gaseous products in the downstream wake zone of the projectile base), and new SRM module was designed for projectile range enhancement. Both propellant compositions and grain shapes were optimised to produce required "thrust" and to withstand severe gun launching conditions - high acceleration and pressure in gun barrel. The research work also includes investigation and optimisation of complex flight mechanics of a gun launched - solid rocket motor propelled - base bleed projectile, as well aerodynamic shape optimisation, and overall modular projectile design optimisation in order to improve payload efficiency. The research work covers theoretical calculations, numerical simulations and their validation through experiments, with results confirming the feasibility of the concept.